2019
DOI: 10.1017/thg.2019.108
|View full text |Cite
|
Sign up to set email alerts
|

Wisconsin Twin Project Overview: Temperament and Affective Neuroscience

Abstract: The Wisconsin Twin Project encompasses nearly 30 years of longitudinal research that spans infancy to early adulthood. The twin sample was recruited from statewide birth records for birth cohorts 1989–2004. We summarize early recruitment, assessment, retention and recently completed twin neuroimaging studies. In addition to the focal twins, longitudinal data were also collected from two parents and nontwin siblings. Our adolescent and young adult neuroimaging sample (N = 600) completed several previous behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In particular, research on adolescent twins showed that genetic influences account for 47% of individual variability in self-reported sensory sensitivity (Assary et al, 2021), in line with studies reporting between 38% and 47% heritability for temperament features (including sensory sensitivity; (Oniszczenko et al, 2003)). Furthermore, sensory processing abilities appear to be stable across the lifespan (Hulle et al, 2015;Lemery-Chalfant et al, 2013;Schmidt et al, 2019), and longitudinal twin studies from adolescence to adulthood show genetic factors contribute to this stability (Kandler et al, 2013). Yet, little is known about the role of genes and environments for differences in sensory processing early in life.…”
Section: Despite a Paucity Of Behavioural Genetics Work Investigating...mentioning
confidence: 99%
“…In particular, research on adolescent twins showed that genetic influences account for 47% of individual variability in self-reported sensory sensitivity (Assary et al, 2021), in line with studies reporting between 38% and 47% heritability for temperament features (including sensory sensitivity; (Oniszczenko et al, 2003)). Furthermore, sensory processing abilities appear to be stable across the lifespan (Hulle et al, 2015;Lemery-Chalfant et al, 2013;Schmidt et al, 2019), and longitudinal twin studies from adolescence to adulthood show genetic factors contribute to this stability (Kandler et al, 2013). Yet, little is known about the role of genes and environments for differences in sensory processing early in life.…”
Section: Despite a Paucity Of Behavioural Genetics Work Investigating...mentioning
confidence: 99%